2015
DOI: 10.15537/smj.2015.9.11844
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of iron deficiency anemia in infants attending a well-baby clinic in northwestern Saudi Arabia

Abstract: Objectives:To determine the prevalence of iron deficiency anemia (IDA) in infants aged 6-24 months attending the well-baby clinic in primary health care centers (PHCCs).Methods:This cross-sectional epidemiological study was conducted in the Northwestern region of Saudi Arabia from April 2013 to January 2014 in 5 randomly selected PHCCs. The sample size comprised 500 infants, with 100 infants screened from each PHC. Blood samples were obtained for estimation of hemoglobin and serum ferritin levels.Results:Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 26 publications
5
37
1
Order By: Relevance
“…Comparably high anemia prevalence has also been previously shown in low-resource Chinese infants and toddlers (51-60% of 6-17-month olds (Hipgrave et al, 2014;Luo et al, 2014)), whereas high IDA has also been found in Saudi Arabian infants (49% at 6-24 months of age; Al Hawsawi et al, 2015). Overall, these comparisons suggest that our population showed a high prevalence of ID, IDA, and anemia even among other low-resource populations.…”
Section: Infant Iron Statussupporting
confidence: 82%
See 1 more Smart Citation
“…Comparably high anemia prevalence has also been previously shown in low-resource Chinese infants and toddlers (51-60% of 6-17-month olds (Hipgrave et al, 2014;Luo et al, 2014)), whereas high IDA has also been found in Saudi Arabian infants (49% at 6-24 months of age; Al Hawsawi et al, 2015). Overall, these comparisons suggest that our population showed a high prevalence of ID, IDA, and anemia even among other low-resource populations.…”
Section: Infant Iron Statussupporting
confidence: 82%
“…Among Latin American countries in a recent review, Bolivia has the highest national prevalence of anemia among preschoolers (6–59-month-olds; 61%; Mujica-Coopman et al, 2015), and so it is perhaps not surprising that our study also showed an extremely high prevalence of anemia in infants, despite our adjustment for the high altitude of the study setting. Comparably high anemia prevalence has also been previously shown in low-resource Chinese infants and toddlers (51–60% of 6–17-month olds (Hipgrave et al, 2014; Luo et al, 2014)), whereas high IDA has also been found in Saudi Arabian infants (49% at 6–24 months of age; Al Hawsawi et al, 2015). Overall, these comparisons suggest that our population showed a high prevalence of ID, IDA, and anemia even among other low-resource populations.…”
Section: | Discussionmentioning
confidence: 55%
“…In a cross-sectional study of 500 Saudi infants aged 6–24 months attending a well-baby clinic, Al Hawsawi et al reported that 49% had IDA (Hb < 11 g/dL, serum ferritin <10 µg/L) [66]. In a study of Saudi school children, Abou-Zeid et al reported 11.6% to be anemic, with a declining rate of anemia from ages 6 to 14 years [60].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Since the fetus depends on the maternal iron level, higher risk women for iron deficiency with concomitant increased risk of anemia among newborn babies. Due to these, anemia in the newborn has serious public health issues in developing countries [11,12].…”
Section: Introductionmentioning
confidence: 99%